2020
DOI: 10.1097/cm9.0000000000000649
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for both-column acetabular fractures using pre-operative virtual simulation and three-dimensional printing techniques

Abstract: Background: Surgical treatment of both-column acetabular fractures is challenging because of the complex acetabular fracture patterns and the curved surface of the acetabulum. Seldom study has compared the application of three-dimensional (3D) printing technology and traditional methods of contouring plates intra-operatively for the surgical treatment of both-column acetabular fractures. We presented the use of both 3D printing technology and a virtual simulation in pre-operative planning for both-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 21 publications
1
38
0
3
Order By: Relevance
“…Previous studies have reported 3-D printing simulated operations improved the accuracy and safety of orthopedic surgeries [22]. Huang et al [23] demonstrated that 3-D printing technology increased the predictability, accuracy and reliability of both-column acetabular fractures reduction.Wang reported that, compared with CT images or humerus-subtracted volume renderings,the 3-D-printed model was able to represent the glenoid bony morphology accurately and clearly which facilitated shoulder surgeons to perform preoperative planning [24]. A double-blinded randomized clinical trial indicated that osteotomy simulation on the 3-D-printed pelvis models for DDH patients increased the success rate of the operation and shortened surgery time ,as well as promoted postoperative recovery [25].Xu et al [26] recommended the use of the 3-D printed model before THA in DDH patients due to better preoperative planning and intraoperative orientation,as well as surgical outcomes.Our study demonstrated the high agreement between the size of the acetabular cup and bone defect of simulated operations on 3-D printing models and the actual size used in the operations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported 3-D printing simulated operations improved the accuracy and safety of orthopedic surgeries [22]. Huang et al [23] demonstrated that 3-D printing technology increased the predictability, accuracy and reliability of both-column acetabular fractures reduction.Wang reported that, compared with CT images or humerus-subtracted volume renderings,the 3-D-printed model was able to represent the glenoid bony morphology accurately and clearly which facilitated shoulder surgeons to perform preoperative planning [24]. A double-blinded randomized clinical trial indicated that osteotomy simulation on the 3-D-printed pelvis models for DDH patients increased the success rate of the operation and shortened surgery time ,as well as promoted postoperative recovery [25].Xu et al [26] recommended the use of the 3-D printed model before THA in DDH patients due to better preoperative planning and intraoperative orientation,as well as surgical outcomes.Our study demonstrated the high agreement between the size of the acetabular cup and bone defect of simulated operations on 3-D printing models and the actual size used in the operations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported 3-D printing simulated operations improved the accuracy and safety of orthopedic surgeries [22]. Huang et al [23] demonstrated that 3-D printing technology increased the predictability, accuracy and reliability of both-column acetabular fractures reduction.Wang reported that, compared with CT images or humerus-subtracted volume renderings,the 3-D-printed model was able to represent the glenoid bony morphology accurately and clearly which faciliated shoulder surgeons to perform preoperative planning [24]. A double-blinded randomized clinical trial indicated that osteotomy simulation on the 3-D-printed pelvis model for DDH patients increased the success rate of the operation and shortened surgery time ,as well as promoted postoperative recovery [25].Xu et al [26] recommended the use of the 3-D printed model before THA in DDH patients due to better preoperative planning and intraoperative orientation,as well as surgical outcomes.Our study demonstrated the high agreement between the size of the acetabular cup and bone defect of simulated operations on 3-D printing models and the actual size used in the operations.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of 3-D printing technology, the individual life-size models allow surgeons to simulate operations and perform precise treatment,as well as improve outcomes [4][5][6].In this study,we developed a new method to restore the hip rotation center by simulating operations on 3-D printing model.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,6 Despite these advantages of TPT, it is not always easy to achieve anatomical reduction of the articular surface of complex AFs because of the limitations in accuracy of the current printing technology and printed materials, lack of a detailed understanding of true anatomical relationships, presence of 3D anisotropy, and the complex anatomical structure of the pelvis. 2,7 These factors markedly increase the risk of an inappropriate pre-bent shape of the reconstructed plate, resulting in an inaccurate length of the screws fixed on the model and ultimate failure to achieve the desired effect. [8][9][10] In this review, we introduce the use of mirror 3D printing model technology (MTT), which involves printing a 3D model of the unaffected acetabulum to reflect the true anatomical relationship, to assess the clinical outcomes of TPT versus MTT for the management of isolated AFs (IAFs).…”
Section: Introductionmentioning
confidence: 99%
“…1,5,6 Despite these advantages of TPT, it is not always easy to achieve anatomical reduction of the articular surface of complex AFs because of the limitations in accuracy of the current printing technology and printed materials, lack of a detailed understanding of true anatomical relationships, presence of 3D anisotropy, and the complex anatomical structure of the pelvis. 2,7…”
Section: Introductionmentioning
confidence: 99%